Low temperature annealing of nanocrystalline Si paste for pn junction formation. (15th November 2021) - Kuboki, Yusuke; Zhu, Huan; Sakamoto, Morihiro; Matsumoto, Hiroshige; Teii, Kungen; Kato, Yoshimine
Abstract: Low temperature annealing of p- and n-type Si paste films consisting of nanocrystal Si particles coated on Al substrates was investigated for application to low cost large-area electronic devices such as solar cells. This process based on aluminum-induced-crystallization enabled one to enhance recrystallization of the Si paste films with reduction of residual tensile stress while suppressing oxidation greatly even at low temperatures (400–550 °C), as confirmed by Raman spectroscopy, X-ray diffraction, and Fourier-transform infrared spectroscopy. pn homo-junction diodes were fabricated successfully using a p/n-type double layer Si paste film and even an n-type single layer Si paste film on Al substrates by annealing at temperatures less than 550 °C. The current-voltage characteristic of the diode using a p/n-type double layer Si paste film showed rectification with the on/off current ratio of about 3200 and the reverse current density of the order of 10 −9 A/cm 2 at room temperature.